Interfacial strength and structure of joining between 2024 aluminum alloy and SiCp/2024 Al composite in semi-solid state. (January 2015) - Cheng, Y.S.; Zhang, X.H.
Highlights: Joined 2024 aluminum alloy and SiCp/2024 composite in semi-solid status. The shear strength of interface had reached to that of SiCp/2024 Al composite. The mechanism of joining in semi-solid was discussed in this paper. Abstract: Semi-solid joining of 2024 aluminum alloy and SiCp/2024 Al composite was investigated based on the shear strength and microstructure of interface. An as-extruded 2024 aluminum alloy was chosen in this study for its fine crystal grain and higher strain energy, which was beneficial to the preparation of semi-solid billet. Then recrystallisation and partial melting method (RAP) was carried out to prepare semi-solid billet of 2024 aluminum alloy. Then the semi-solid 2024 aluminum alloy was joined with the SiCp/2024 Al composite, which was also in the semi-solid state, at/under different temperatures/pressures. Shear test was performed to measure the interfacial strength. Scanning electron microscope (SEM) was used to observe the microstructure of interface. The results showed that the shear strength of interface had reached to that of SiCp/2024 Al composite. The shear strength increased as the applied pressure increasing, and had a close relationship with temperature. The mechanism of semi-solid joining with pressure was that the mixture of two kinds of base materials, accompanying with the diffusion of atom at high temperatures. It should be pointed out that the microstructure of interface was much finer than that of the substrate, due to the nucleation promotion of SiC particle in the solidification process.